LIGHT ELECTRIC VEHICLE POWERTRAIN ANALYSIS - Andrzej ŁEBKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
This paper describes the structure of a light electric vehicle known as the Mia Electric vehicle. The vehicle parameters and exploitation properties are presented, while the advantages and disadvantages of the vehicle’s technical solutions are discussed, along with possible ideas for their improvement. Vehicle test results on a roller dyno and under actual driving conditions are presented. The data recorded during tests form the basis of an analysis of the vehicle powertrain, whose findings are described in the summary along with testing conclusions.